Histamine receptor 1 inhibition enhances antitumor therapeutic responses through extracellular signal-regulated kinase (ERK) activation in breast cancer. (28th June 2018) - Fernández-Nogueira, Patricia; Noguera-Castells, Aleix; Fuster, Gemma; Recalde-Percaz, Leire; Moragas, Núria; López-Plana, Anna; Enreig, Estel; Jauregui, Patricia; Carbó, Neus; Almendro, Vanessa; Gascón, Pedro; Bragado, Paloma; et al.
Abstract: Histamine receptor 1 (HRH1) belongs to the rhodopsin-like G-protein-coupled receptor family. Its activation by histamine triggers cell proliferation, embryonic development, and tumor growth. We recently established that HRH1 is up-regulated in basal and human epidermal growth factor receptor 2 (HER2)-enriched human breast tumors and that its expression correlates with a worse prognosis. Nevertheless, the functional role of HRH1 in basal and HER2-targeted therapy-resistant breast cancer (BC) progression has not yet been addressed. Using terfenadine, a selective chemical inhibitor of HRH1, we showed that the inhibition of HRH1 activity in basal BC cells leads to sub-G0 cell accumulation, suppresses proliferation, promotes cell motility and triggers the activation of extracellular signal-regulated kinase( ERK) signaling, initiating the mitochondrial apoptotic pathway. Furthermore, HER2-targeted therapy-resistant cells express higher levels of HRH1 and are more sensitive to terfenadine treatment. Moreover, in vivo experiments showed that terfenadine therapy reduced the tumor growth of basal and trastuzumab-resistant BC cells. In conclusion, our results suggest that targeting HRH1 is a promising new clinical approach to consider that could enhance the effectiveness of current therapeutic treatment in patients with basal and BC tumors resistant to HER2-targeted therapies. Highlights: HRH1 is overexpressed in basal and HER2 targeted therapies resistant BC cells. HRH1 inhibition induces apoptosis in basal cells through ERK activation. Treatment with terfenadine, HRH1 inhibitor, inhibits basal cells migration. Terfenadine treatment inhibits basal and trastuzumab resistant cells tumor growth.